Morphological and Molecular Identification of Colletotrichum spp. Associated with Chili Anthracnose Disease in Yogyakarta Region - Dhika Sri Anggrahini; Arif Wibowo; Siti Subandiyah (Universitas Gadjah Mada, 2020)
Colletotrichum sp., the causal agent of anthracnose disease, is one of the important pathogenic fungi in chili which can cause considerable yield losses, especially during the rainy season. This study aimed to identify the species of Colletotrichum isolates obtained from chili cultivation area in The Special Region of Yogyakarta Province both morphologically and molecularly. As a comparison, a Colletotrichum isolate obtained from Magelang Regency, Central Java Province was used as comparison isolate. From the isolation result, it was obtained 14 isolates of Colletotrichum that generally had conidia that were fusiform to cylindrical with two pointed or slightly blunt ends, or crescent shapes with a various size range between 9.02-19.38 µm x 2.37–8.57 µm. Based on morphological observations using UPGMA analysis, these 14 isolates could be divided into 4 groups with 7 different types. Representative isolates of each type in different groups and a comparison isolate were identified molecularly by multi-gene analysis using the ITS1-4, gapdh and tub2 genes. The result showed that B1, G1, K2 and Mg isolates were closely related to Colletotrichum scovillei, J1 with C. truncatum; S1 and S2 with C. siamense; and J2 with C. makassarii. From the pathogenicity test on wounded chili, it showed that C. scovillei and C. siamense isolates had higher virulence than C. truncatum and C. makassarii isolates.